Edgar and Brigitte : a German Jewish passage to America - Bodenheimer, Rosemarie, 1946- (Tuscaloosa, Alabama : The University of Alabama Press, 2016)
""Edgar and Brigitte" is the fruit of an extraordinary archive of personal journals, letters, speeches, and published writings left by Edgar and Brigitte Bodenheimer, who emigrated from Nazi Germany in 1933 and became American law professors"--
1. Coming of age in the Weimar Republic -- 2. Emigration -- 3. Brigitte Levy -- 4. Seattle -- 5. Back East, out West -- 6. Returns -- 7. Family law, natural law -- 8. Gray lady -- 9. Family life in Salt Lake city.
Includes bibliographical references and index.
Print version record.
Keywords: Bodenheimer, Edgar, -- 1908-1991.; Bodenheimer, Brigitte M; Jews -- Germany -- Biography; Jews, German -- United States -- Biography; Immigrants -- United States -- Biography; Jewish law teachers -- United States -- Biography; BIOGRAPHY & AUTOBIOGRAPHY -- Social Scientists & Psychologists; SOCIAL SCIENCE -- Discrimination & Race Relations; SOCIAL SCIENCE -- Minority Studies; Immigrants; Jewish law teachers; Jews; Jews, German; Germany; United States; Electronic books; Biography